2021
DOI: 10.1055/s-0041-1735150
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcome of Sepsis in Recipients of Solid Organ Transplant

Abstract: Sepsis is a complex disease stemming from a dysregulated immune response toward an infectious agent. In transplantation, sepsis remains one of the leading causes of morbidity and mortality. Solid organ transplant recipients have impaired adaptive immunity due to immunosuppression required to prevent rejection. Immunosuppression has unintended consequences, such as increasing the risk of infections and sepsis. Due to its high morbidity and mortality, early detection of sepsis is paramount to start aggressive tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
(135 reference statements)
1
5
0
Order By: Relevance
“…It is often assumed that SOT recipients experience worse outcomes from BSI due to their immunosuppression. 12 However, we 13,14 and others [15][16][17] recently provided evidence to the contrary. In a small pilot matched prospective cohort study comparing SOT and immunocompetent, non-SOT recipients with Staphylococcus aureus, Escherichia coli, or Klebsiella pneumoniae bacteremia, we found that mortality did not significantly differ by transplant status.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…It is often assumed that SOT recipients experience worse outcomes from BSI due to their immunosuppression. 12 However, we 13,14 and others [15][16][17] recently provided evidence to the contrary. In a small pilot matched prospective cohort study comparing SOT and immunocompetent, non-SOT recipients with Staphylococcus aureus, Escherichia coli, or Klebsiella pneumoniae bacteremia, we found that mortality did not significantly differ by transplant status.…”
Section: Introductionmentioning
confidence: 60%
“…The clinical characteristics contributing to the outcome of SOT recipients who develop Gram‐negative bacteremia (GNB), however, are incompletely understood. It is often assumed that SOT recipients experience worse outcomes from BSI due to their immunosuppression 12 . However, we 13,14 and others 15–17 recently provided evidence to the contrary.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the ICU, bacteremia arising from vascular catheter colonization is an important cause of patient destabilization[ 35 ]. MDRO bacteremia, in particular, is a recognized cause of sepsis in the ICU[ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity is defined as the disease or status that may affect the prognosis of septic patient, such as cancer, autoimmune disease, chronic kidney disease, chronic liver disease, coronary artery disease, diabetes mellitus, hypertension, hyperlipidemia and history of organ transplantation [ 12 , 13 ].¸ [ [14] , [15] , [16] , [17] , [18] , [19] ]. The past medical history is confirmed by corresponding ICD coding ever documented in electronic medical records within the past year before hospital admission.…”
Section: Methodsmentioning
confidence: 99%